Perceptions and Challenges of Hybrid Learning in Islamic Education: A Comparative Study of Lecturers and Students - Sahib, Abdul; Gusmuliana, Paidi; Amrina, Rizqy Dwi; Baihaqi, Yasmika; Gunawan, Guntur; Rizal, Syamsul (Journal of Teaching and Learning, 2026)
This study explored the perceptions, challenges, and expectations of lecturers and students at IAIN Curup and UIN Raden Fatah Palembang regarding hybrid learning in Islamic education. Using a mixed-methods design, the study combined quantitative data from 150 students and 20 lecturers collected through closed-ended questionnaires with qualitative insights from semi-structured interviews. The findings indicated that while 80.4% of lecturers and 63% of students supported hybrid learning, significant challenges remain, including inadequate technological infrastructure, high costs, and insufficient faculty training. Participants emphasized the need for better resource allocation, improved infrastructure, and stronger support systems to enhance learning outcomes. Findings suggest that addressing these barriers is critical for the successful implementation of hybrid learning in Islamic education contexts. Furthermore, integrating technological advancements with Islamic educational principles is essential. This paper offers specific policy recommendations to overcome these challenges and enhance the quality of Islamic education in the region, as well as valuable guidance for stakeholders seeking to adapt to modern educational trends while preserving Islamic educational values.